PENGARUH UMUR POHON INDUK, UMUR TUNAS DAN JENIS MEDIA TERHADAP PERTUMBUHAN STEK PUCUK SUKUN - Hamdan Adma Adinugraha (Jurnal Pemuliaan Tanaman Hutan, 2011)
The study was  conducted to develop methods for  planting stock production by shoot cuttings. The objectives of the study were to identify the effect of parent tree age, shoot age and  rooting media on the growth of shoot cuttings. The study was conducted in 2 experimental steps. The first was  to examine the  effect of  parent tree age and shoot age  on the groeth of cutting: parent tree age class of 5 years (KU-1), 6-10 years (KU-2), 11-15 years (KU-3) and 16-20 years  (KU-4), and shoot ages of  3 and 4 months. The second  was to test 6  rooting media types  (volcanic sands, soil, rice husk charcoal, coconut husk, sand + rice husk charcoal/4:1 and sand + coconut husk/4:1). The results showed that shoot cuttings from root cuttings grew successfully. It reached 90-100% of survival rate. Parent tree age  and shoot age significantly influenced the  number of roots with the highest root number was 5,42 from 4 months shoot taken from KU-4 root cuttings.  Types  of media  significantly affected  rooting rate with the best was 98% shown  in sand + rice husk charcoal (4:1) media.